2017
DOI: 10.1002/ajmg.a.38183
|View full text |Cite
|
Sign up to set email alerts
|

Functional monosomy of 6q27‐qter and functional disomy of Xpter‐p22.11 due to X;6 translocation with an atypical X‐inactivation pattern

Abstract: Pattern of X chromosome inactivation (XCI) is typically random in females. However, chromosomal rearrangements affecting the X chromosome can result in XCI skewing due to cell growth disadvantage. In case of an X;autosome translocation, this usually leads to an XCI pattern of 100:0 with the derivative X being the active one in the majority of females. A de novo balanced X;6 translocation [46,X,t(X;6)(p22.1;q27)] and a completely skewed XCI pattern (100:0) were detected in a female patient with microcephaly, ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In this female, in contrast to what normally happens, the wild-type X chromosome remained active in all her cells, probably as a result of selection against cells that contained the non-functional POLA1. 33 DNA-fiber-combing analysis did reveal a reduction in new initiation events in the family C proband's LCLs of 5.9% (n ¼ 170 fibers), compared to 9.6% (n ¼ 178 fibers) observed in the paternal LCLs, a difference indicative of impaired ''productive'' replication initiation. 34,35 Consistent with this, we also observed increased inter-origin distance (IOD) in the family C proband's LCLs compared to those of the father ( Figure 3B).…”
mentioning
confidence: 78%
“…In this female, in contrast to what normally happens, the wild-type X chromosome remained active in all her cells, probably as a result of selection against cells that contained the non-functional POLA1. 33 DNA-fiber-combing analysis did reveal a reduction in new initiation events in the family C proband's LCLs of 5.9% (n ¼ 170 fibers), compared to 9.6% (n ¼ 178 fibers) observed in the paternal LCLs, a difference indicative of impaired ''productive'' replication initiation. 34,35 Consistent with this, we also observed increased inter-origin distance (IOD) in the family C proband's LCLs compared to those of the father ( Figure 3B).…”
mentioning
confidence: 78%
“…Even though females with intact X chromosomes usually present a random choice of which one becomes inactivated, in females that carry structural alterations on the X chromosome, cells with the least genomic imbalances are positively selected, which commonly results in a skewed inactivation (Podolska et al, 2017; Schluth et al, 2006). In X‐autosome translocations, which affect 1 in 30,000 live births (Dell'Edera et al, 2012), the skewness of XCI depends on whether the translocation is balanced or unbalanced (Leppig & Disteche, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In unbalanced X;autosome translocations, the normal X is mainly the active chromosome to compensate for the deleted or duplicated region on the translocated X. Mohamed et al [2018] reported an alternative X inactivation between the normal X and the unbalanced translocated X to compensate for the deletion and duplication of the un-balanced translocated X and the extension of the X inactivation to certain regions on chromosome 14 [Cottrell et al, 2009;Gläser et al, 2004;Podolska et al, 2017;Mohamed et al, 2018].…”
mentioning
confidence: 99%